Paleoenvironmental context and significance of a partial elasmosaurid skeleton from the Albian of Haute-Provence, France. (April 2020) - Vincent, P.; Grosjean, A.-S.; Bert, D.; Ferreira, J.; Suchéras-Marx, B.; Suan, G.; Guinot, G.; Perrier, V.; Janneau, K.; Brazier, J.-M.; Sarroca, E.; Guiomar, M.; et al.
Abstract: The Early–Late Cretaceous transition (late Albian–early Cenomanian; 100 Ma) witnessed marked environmental changes and a deep reorganization of the marine fauna. The impact of these environmental and biotic changes on Tethyan marine vertebrates is poorly understood, due to a fragmentary fossil record. Here we report upper Albian marine vertebrate remains, including a partially articulated plesiosaurian skeleton, from a fossiliferous glauconite-rich bed in the Alpes de Haute-Provence, France. The fossiliferous horizon produced a diversified invertebrate fauna including ammonoids and belemnoids. The ammonite fauna is abundant and diversified, indicating the Mortoniceras fallax ammonite Zone. The calcareous nannofossil biomarkers date the bed to the NC10a Zone. The fossiliferous bed consists of glauconitic marls enriched in planktic foraminifera and occurs amongst a monotonous succession of alternating marlstones and limestone beds. The vertebrate fauna consists of chondrichthyans and marine reptiles. Chondrichthyans are represented by five Lamniformes species (dominated by Sphenodus ) and comprise predator taxa probably living in open marine temperate waters. The site yielded a large, partial post-cranial plesiosaurian skeleton with articulated elements, belonging to an elasmosaurid and representing one of the most complete Albian plesiosaurian specimens known from Europe. The abundance and preservation of the collected fossil remains are best explained by their concentration during a basin-scale episode of very low sedimentation corresponding to a major episode of marine transgression, associated with a lower oxygenation of bottom waters. These findings indicate that the newly discovered fossiliferous bed holds promising clues about the evolutionary history of major groups of marine vertebrates and ammonites near the Early–Late Cretaceous transition. Highlights: We report an Albian Konzentrat-Lagerstätte from the Pre-Alps in SE France. Fossil remains consist of ammonites, chondrichthyans, ichthyosaurs and plesiosaurs. The most complete plesiosaur specimen from the Albian strata of France is described.